Trust mechanisms: an integrated approach for e-commerce website development process - Othman, N.Z.; Hussin, A.R.C.; Rakhmadi, A. (2008)
Trust is a crucial element to the success of e-commerce implementation. The research on the concept of trust has emerged rapidly due to the need of understanding trust in order to improve current and future e-commerce implementation. Although there are various researches conducted focusing on different aspect of trust, there are only few that provide a practical guideline to build a trusted e-commerce website. This research aims to find a practical solution on how to integrate trust during the development process of an e-commerce website and to test the constructed website in a real world situation. It will also propose a model that shows how consumer trust is developed and communicated during the engagement of consumers in e-commerce activities. This research found that there are six categories of trust mechanisms that web merchants can adopt in order to integrate trust in their website. It will provide well tested guidelines for web merchants to understand about consumer trust in order for them to design and develop a secure and trusted e-commerce website.